Komparasi Terhadap Konsep Vasudhaiva Kutumbakam Dan Ukhuwah Insanniyah: Implementasinya Dalam Menjaga Kerukunan Pasca Konflik Antar Umat Beragama Di Kota Mataram - John Abraham Ziswan Suryosumunar (Jayapangus Press, 2021)
Cross religious studies is important to do in a multicultural society, such as Indonesia. This is because of the potential breakdown that can occur. The social breakdown appeared in various conflicts, one of which occurred between Hindu-Balinese and Muslim-Sasak in Mataram city. This conflict, which often result in problems of tolerance, not only creates chaos but also leaves sensitivity to both of groups that can potentially lead to new conflict. It is necessary to do internalization of awareness about the importance of unity based on the teachings of each religions. The author in this study attempted to conduct cross religious studies in the field of religious philosophy. The author tried to explore and compare the concept of the brotherhood of humanity in Islam, namely ukhuwah insanniyah concept, and the concept of vasudhaiva kutumbakam from Hinduism, as well as explore its relevance in maintaining harmony post-conflict in Mataram. As a research in the field of philosophy, this research uses the philosophical hermeneutic method, with the source of library data. The conclusions of this study: (1) the concept of vasudhaiva kutumbakam is the concept of the whole world family, this concept comes from the Veda, especially the Maha Upanisad. Meanwhile, the concept of ukhuwah insanniyah is the concept of universal brotherhood between mankind which refers to the Qur'an and hadith. (2) Both of concept based on universal relationship, but in the meaning of diversity, the concept of vasudhaiva kutumbakam emphasizes that every being is the same(tat tvam asi) in one family, while the concept of ukhuwah insanniyah emphasizes diversity as a necessity through which every human being can know each other. (3) Both concepts can encourage the emergence of awareness of unity and tolerance among religious communities in Mataram.